System princip of biology - Безродный, А. Г. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Using a systematic approach to describe the various states of biological objects is a permanent attribute of scientific research. However, the concept of "system" and implies that they are a methodological approach in the scientific literature often treated differently. Here’s a definition, for example, gives one of the founders of the theory of systems L. Bertalanfy: "The system is a complex of elements found in the interaction". V. Sadovsky in his book "Fundamentals of general systems theory" gives about forty different interpretations of the concept of the system. And often, these definitions are mutually exclusive. N.V. Blauberg and B.G. Yudin, describing the system, indicate: "Communication, integrity and due to their stable structure – these are the features of any system". Thus, the presence of elementary units and their interaction are the main features of the system. The article analyzes the use of systems analysis in biology. Emphasized the basic provisions of the system and given him a chariot Brief description. Comparisons between themselves integrative and additive systems. The basic system of living factors. The author gives an outline of the main provisions of the modern systematization.